2021
DOI: 10.3390/axioms10010033
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the EBM Model and LTS(A,A,A) Model to Evaluate the Efficiency in the Supply Chain of Packaging Industry in Vietnam

Abstract: In recent decades, Vietnamese labeling and packaging has been widely recognized as being one of the fastest developing industries in Vietnam, supported by the tremendous demand of domestic production and the exportation of its packaged goods. The emerging packaging technology trends and the participation of foreign direct investment (FDI) companies have led to fierce competition between all packaging enterprises in Vietnam. This paper aims to calculate the productivity performance of 10 packaging companies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This recent study showed most of the global trade is seaborne and plays an important role in the national economy of a country. Using the EBM and LTS models, Vietnam was identified as one of the fastest-growing industries, Wang et al [16] integrated these models in evaluating the supply chain of the packaging industry that showed a result that one company in Vietnam achieved a strong efficiency score and high productivity. The DEA method can be used as well in senior care facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This recent study showed most of the global trade is seaborne and plays an important role in the national economy of a country. Using the EBM and LTS models, Vietnam was identified as one of the fastest-growing industries, Wang et al [16] integrated these models in evaluating the supply chain of the packaging industry that showed a result that one company in Vietnam achieved a strong efficiency score and high productivity. The DEA method can be used as well in senior care facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EBM model and gray forecasting were used by Wang et al [28] to evaluate the efficiency of third-party logistics services. Wang et al [29] used the EBM model and the LTS (A, A, A) model to assess the efficiency of the packaging industry's supply chain in Vietnam. The found that the packaging business as a whole has a high level of productivity.…”
Section: Epsilon-based Measure (Ebm)mentioning
confidence: 99%
“…This framework contains two parameters, one scalar and one vector, which are defined by affinity index in relation to the inputs and outputs. These two factors are used to combine the radial and non-radial models into a single model for evaluating DMU efficiency [29].…”
Section: Epsilon-based Measure Efficiencymentioning
confidence: 99%
See 2 more Smart Citations